2013
DOI: 10.1016/j.brs.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial Direct Current Stimulation (tDCS) on cortical activity: A computational modeling study

Abstract: Although it is well-admitted that transcranial Direct Current Stimulation (tDCS) allows for interacting with brain endogenous rhythms, the exact mechanisms by which externally-applied fields modulate the activity of neurons remain elusive. In this study a novel computational model (a neural mass model including subpopulations of pyramidal cells and inhibitory interneurons mediating synaptic currents with either slow or fast kinetics) of the cerebral cortex was elaborated to investigate the local effects of tDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 49 publications
4
98
0
Order By: Relevance
“…We here simulate the effects of tDCS by simply adding an additional current to the pyramidal cells and inhibitory interneurons, based on values from simulations reproducing tDCS-induced changes in sensory-evoked potentials in vivo (Molaee- Ardekani et al, 2013) and current understanding of the mechanism of action of tDCS (Bikson et al, 2004;Bindman et al, 1964;Funke, 2013;Nitsche and Paulus, 2011;Radman et al, 2009;Rahman et al, 2013). Specifically, depolarizing (anodal) stimulation was simulated by adding depolarizing current into each pyramidal cell and hyperpolarizing current into each interneuron, while hyperpolarizing (cathodal) current was simulated by adding hyperpolarizing current into pyramidal cells and depolarizing current into interneurons.…”
Section: Simulating Tdcs-induced Currents In a Neural Network Modelmentioning
confidence: 99%
“…We here simulate the effects of tDCS by simply adding an additional current to the pyramidal cells and inhibitory interneurons, based on values from simulations reproducing tDCS-induced changes in sensory-evoked potentials in vivo (Molaee- Ardekani et al, 2013) and current understanding of the mechanism of action of tDCS (Bikson et al, 2004;Bindman et al, 1964;Funke, 2013;Nitsche and Paulus, 2011;Radman et al, 2009;Rahman et al, 2013). Specifically, depolarizing (anodal) stimulation was simulated by adding depolarizing current into each pyramidal cell and hyperpolarizing current into each interneuron, while hyperpolarizing (cathodal) current was simulated by adding hyperpolarizing current into pyramidal cells and depolarizing current into interneurons.…”
Section: Simulating Tdcs-induced Currents In a Neural Network Modelmentioning
confidence: 99%
“…114 Moreover, modeling and MRI studies indicate that anodal polarization may also affect excitability in inhibitory interneurons. 115,116 The behavioral consequences of NIBS could, therefore, be strictly related to the emergent properties of the stimulated networks, also considering the fact that an increase in excitability does not necessarily mean an increase in processing efficacy and vice versa. 112 …”
Section: Neurorehabilitation and Nibsmentioning
confidence: 99%
“…It was assumed that the perturbation is linearly related to the stimulus amplitude and direction dependent (relative to the stimulus field). Interestingly, Molaee-Ardekani et al (2013) found that only when including an effect of the stimulation field on interneuron populations, the model produced a better prediction of experimental measurements. Finally, at the population level, the modeling of the TCS stimulation can be combined with the FEM approach, where MRI-derived head models inform the positioning of neural populations, and a realistic electric field is simulated .…”
Section: Noninvasive Electric Stimulationmentioning
confidence: 93%
“…Extrapolating from the detailed models in network models point neurons have been used, where only 1 Introduction pyramidal neurons are affected by the stimulation due to their geometry (Reato et al, 2010). On the neural population level, a similar extrapolation has been used, where the stimulus was modeled as a perturbation on the mean membrane potential of populations (Ali et al, 2013;Dutta and Nitsche, 2013;Molaee-Ardekani et al, 2013). It was assumed that the perturbation is linearly related to the stimulus amplitude and direction dependent (relative to the stimulus field).…”
Section: Noninvasive Electric Stimulationmentioning
confidence: 99%